2020
DOI: 10.1021/acssuschemeng.9b07047
|View full text |Cite
|
Sign up to set email alerts
|

N,F-Codoped Carbon Nanocages: An Efficient Electrocatalyst for Hydrogen Peroxide Electroproduction in Alkaline and Acidic Solutions

Abstract: Exploiting efficient electrocatalysts for hydrogen peroxide (H2O2) electroproduction by oxygen reduction reaction (ORR) is highly desired in practical application. Herein, nitrogen- and fluoride-codoped carbon nanocages (NF-Cs) are successfully synthesized through a simple and scalable template method. With the aid of a porous structure, a large surface area, and the introduction of N and F atoms, NF-Cs show excellent electrocatalytic performance for H2O2 electroproduction in alkaline solution (pH 13) with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 57 publications
1
54
0
Order By: Relevance
“…The doped N atom promotes oxygen adsorption on the catalyst surface, thus improving the catalytic performance for the ORR. Meanwhile, the doped F atom facilitates the desorption of the *OOH intermediate, leading to a high H 2 O 2 selectivity [79] . The N, F‐codoped carbons present catalytic performance for H 2 O 2 generation in both acid and alkaline electrolytes with a high faradaic efficiency (88 %, pH 0.35, 0.72 V; 89.6 %, pH 13, 0.74 V) and excellent stability.…”
Section: Two‐electron Orr Over Carbon Nanomaterialsmentioning
confidence: 99%
“…The doped N atom promotes oxygen adsorption on the catalyst surface, thus improving the catalytic performance for the ORR. Meanwhile, the doped F atom facilitates the desorption of the *OOH intermediate, leading to a high H 2 O 2 selectivity [79] . The N, F‐codoped carbons present catalytic performance for H 2 O 2 generation in both acid and alkaline electrolytes with a high faradaic efficiency (88 %, pH 0.35, 0.72 V; 89.6 %, pH 13, 0.74 V) and excellent stability.…”
Section: Two‐electron Orr Over Carbon Nanomaterialsmentioning
confidence: 99%
“…Non-noble metal-based SACs have also exhibited apparent ORR activity towards H 2 O 2 production. Carbon derivatives are generally used as the supporting matrices [5,16,[67][68][69][70][71][72]. For instance, graphene and carbon nanotubes doped with O, N, F, B, etc have been used rather extensively, into which a range of transition metal atoms (e. g., Co, Ni, Fe, Mn, Cu, etc.)…”
Section: Non-noble Metal Sacsmentioning
confidence: 99%
“…As for noble-metal-free cathodes, there are several reports on the use of carbon-based materials modied with inexpensive metal compounds mainly at basic pH. [38][39][40][41] However, efficiencies for the H 2 O 2 production with these cathodes were low at near-neutral pH, and an ion-exchange membrane was essential when the pH values of the anodic and cathodic electrolyte solutions were different. 21,22 Recently, we reported that a carbon cathode modied with a biomass-derived W-based electrocatalyst exhibited a relatively high cathodic current for the reductive H 2 O 2 production in a nearneutral KHCO 3 aqueous solution in a two-compartment cell, but the FE(H 2 O 2 ) and the partial current density for H 2 O 2 production were not enough.…”
Section: Introductionmentioning
confidence: 99%